Effect of experimental change in children's sleep duration on television viewing and physical activity. Issue 6 (15th July 2016) - Hart, C. N.; Hawley, N.; Davey, A.; Carskadon, M.; Raynor, H.; Jelalian, E.; Owens, J.; Considine, R.; Wing, R. R.
Summary: Background: Paediatric observational studies demonstrate associations between sleep, television viewing and potential changes in daytime activity levels. Objective(s): To determine whether experimental changes in sleep lead to changes in children's sedentary and physical activities. Methods: Using a within‐subject counterbalanced design, 37 children 8–11 years old completed a 3‐week study. Children slept their typical amount during a baseline week and were then randomized to increase or decrease mean time in bed by 1.5 h/night for 1 week; the alternate schedule was completed the final week. Children wore actigraphs on their non‐dominant wrist and completed 3‐d physical activity recalls each week. Results: Children reported watching more television ( p  < 0.001) and demonstrated lower daytime actigraph‐measured activity counts per epoch ( p  = 0.03) when sleep was decreased (compared with increased). However, total actigraph‐measured activity counts accrued throughout the entire waking period were higher when sleep was decreased (and children were awake for longer) than when it was increased ( p  < 0.001). Conclusion(s): Short sleep during childhood may lead to increased television viewing and decreased mean activity levels. Although additional time awake may help to counteract negative effects of short sleep, increases in reported sedentary activities could contribute to weight gain over time.